Classification of normal swallowing and oropharyngeal dysphagia using wavelet - Spadotto, Andre Augusto; Gatto, Ana Rita [UNESP]; Guido, Rodrigo Capobianco; Montagnoli, Arlindo Neto [UNESP]; Cola, Paula Cristina [UNESP]; Pereira, Jose Carlos; Schelp, Arthur Oscar [UNESP] (Elsevier B.V., 2009)
Oropharyngeal dysphagia is characterized by any alteration in swallowing dynamics which may lead to malnutrition and aspiration pneumonia. Early diagnosis is crucial for the prognosis of patients with dysphagia, and the best method for swallowing dynamics assessment is swallowing videofluoroscopy, an exam performed with X-rays. Because it exposes patients to radiation, videofluoroscopy should not be performed frequently nor should it be prolonged. This study presents a non-invasive method for the pre-diagnosis of dysphagia based on the analysis of the swallowing acoustics, where the discrete wavelet transform plays an important role to increase sensitivity and specificity in the identification of dysphagic patients. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Swallowing dynamics; Dysphagia; Discrete wavelet transform; Pattern classification